PENERAPAN STRATEGI CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Siwi Enggar Makarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in Social Studies (IPS). This is characterized by the average Social Studies student score of 59.10, with the percentage of students achieving learning completeness at 50.00% out of 20 students. This research is a classroom action research (PTK) that aims to improve student learning outcomes in IPS through the implementation of Contextual Teaching and Learning (CTL) strategies. This study was conducted in 010 primary schools in Silikuan Ukui Hulu subdistrict, with research subjects being fifth-grade students, totaling 20 students. This study was conducted over two cycles. The data used in this study are the activities of teachers, student activities, and learning outcomes, which are collected using observation techniques for teacher and student activities and written tests. The analytical technique used in this research is descriptive analysis. The study states that the acquisition of teacher and student activities and learning outcomes has increased in each cycle. This is supported by: (1) the percentage of teacher activity in the first cycle, first meeting, at 45%; in the first cycle, second meeting, the percentage of teacher activity at 52%; the percentage of teacher activity in the second cycle, first meeting, at 65%; the percentage of teacher activity in the second cycle, second meeting, at 75%; (2) the percentage of student activity in the first cycle, first meeting, at 49%; in the first cycle, second meeting, the percentage of student activity at 60%; the percentage of student activity in the second cycle, first meeting, at 63%; the percentage of student activity in the second cycle, second meeting, at 79%; (3) learning outcomes with a baseline score of 59.10, and only 10 students (50%) reached the KKM (Minimum Completeness Criteria) of 65. In the first cycle, the average value obtained by the students reached 63.6, with 13 students (65%) achieving the KKM. In Cycle II, the average value obtained by students achieved a value above 67, meaning they surpassed the KKM. In the end, 16 students (80%) reached the KKM.